Implications of tolerance to iron toxicity on root system architecture changes in rice (Oryza sativa L.) - Sonu; Nandakumar, Shekharappa; Singh, Vikram Jeet; Pandey, Rakesh; Gopala Krishnan, Subbaiyan; Bhowmick, Prolay Kumar; Ellur, Ranjith Kumar; Bollinedi, Haritha; Harshitha, Bheemapura Shivakumar; Yadav, Sunaina; Beniwal, Ravina; Nagarajan, Mariappan; et al. (Frontiers in Sustainable Food Systems, 2024)
Iron toxicity exerts detrimental effects on rice plant growth during both vegetative and reproductive stages, particularly in lowland rice areas with acidic soils. Excessive iron hampers the absorption of vital macronutrients, including phosphorus and potassium. In this study, we conducted a comprehensive evaluation of the phenotypic response of 16 rice genotypes to various induced iron levels in a hydroponic system. Our results indicate that 460 ppm of iron in the nutrient solution is a critical threshold for screening genotypes in their seedling stage for their response to iron toxicity.The impact of excess iron on morphological and root system characteristics allowed us to classify the genotypes into tolerant and sensitive categories. Notably, leaf bronzing emerged as a major response to iron stress, signifying a clear demarcation between tolerant and sensitive genotypes. A stress stability index, assessed across various traits, provided a robust basis for classification. In addition to known excess iron-tolerant genotypes, we identified ILS12-5 as a previously unrecognized tolerant variety.Conversely, some of the most sensitive genotypes included popular mega varieties such as BPT 5204 and Pusa 44.Iron toxicity exhibited a severe effect on root system architectural traits, specifically root length (RL), surface area (SA), and volume (RV). Our findings shed light on the influence of toxic iron levels on the root system, suggesting that the observed responses in aerial biomass are consequential to root system damage, resulting in nutrient deprivation. Additionally, we propose that iron exclusion may be a major mechanism for developing tolerance in genotypes by reducing Fe 2+ uptake. This is a provisional file, not the final typeset article These findings offer valuable insights for the management of iron toxicity and the enhancement of tolerance in rice through selective breeding programs. However, further field evaluations of identified tolerant and sensitive lines are necessary to confirm their behaviour under natural conditions and their potential for incorporation into breeding programs. Furthermore, investigating the effect of iron toxicity on root system architectural traits can contribute to a deeper understanding of the intrinsic mechanisms that differentiate tolerant from sensitive genotypes.